1368. Assessment of the In Vivo Efficacy of Human-Simulated Epithelial Lining Fluid (ELF) Exposure of Meropenem/Nacubactam (MEM/NAC) Combination Against β-Lactamase-Producing Enterobacteriaceae in Neutropenic Lung Infection Model. (26th November 2018) - Asempa, Tomefa E; Motos, Ana; Abdelraouf, Kamilia; Bissantz, Caterina; Zampaloni, Claudia; Nicolau, David P
Abstract: Background: NAC is a novel dual action β-lactamase inhibitor with in vitro activity against class A, class C, and some class D β-lactamases and antibacterial activity against Enterobactaeriaceae . NAC is being developed as a combination therapy with MEM for the treatment of serious Gram-negative bacterial infections. This study evaluated the efficacy of the human-simulated ELF exposure of MEM/NAC, compared with those of MEM or NAC alone against β-lactamase-producing Enterobacteriaceae isolates in the neutropenic murine lung infection model. Methods: Eight clinical MEM-resistant Enterobacteriaceae isolates harboring various β-lactamases (IMI, KPC, OXA, TEM, SHV, and AmpC) were utilized in the study. MEM and MEM:NAC (1:1) combination MICs were determined in triplicate via broth microdilution. ICR mice were rendered transiently neutropenic, and lungs were inoculated with 50 µL bacterial suspensions of 10 7 CFU/mL. Regimens in mice that simulated the human ELF exposures following doses of MEM 2g q8h and NAC 2g q8h (1.5 hours infusions) as monotherapies and in combination were established. Treatment mice received MEM human-simulated regimen (HSR), NAC HSR, or MEM/NAC HSR and control mice were vehicle-dosed. Treatment was started 2 hours after inoculation and continued for 24 hours. Efficacy was assessed as the change in log10 CFU/lung at 24 hours compared with 0 hours controls. Results: MEM and MEM/NAC MICs were 8–512 and 0.5–8 mg/L, respectively. The average log10 CFU/lung at 0 hours across all isolates was 6.26 ± 0.26. Relative to 0 hours control, the mean bacterial growth at 24 hours in the untreated control mice, MEM HSR, and NAC HSR treatment groups were 2.93 ± 0.29, 2.72 ± 0.42, and 1.75 ± 0.80 log10 CFU/lung, respectively. MEM/NAC HSR resulted in up to 2-log bacterial reduction in isolates with MEM/NAC MIC ≤4 mg/L. Conclusion: MEM/NAC human-simulated ELF exposure produced enhanced efficacy against MEM-resistant β-lactamase-producing Enterobacteriaceae isolates with MEM/NAC MIC ≤4 mg/L. These data support a potential role for MEM/NAC for treatment of lung infections due to β-lactamase-producing Enterobacteriaceae and warrant further studies. This project has been funded in part under HHS BARDA Contract HHSO100201600038C. Disclosures: C. Bissantz, F Hoffmann La Roche Ltd.: Employee, Salary. C. Zampaloni, F. Hoffmann-La Roche Ltd.: Employee, Salary. D. P. Nicolau, Hoffmann-La Roche Ltd.: Grant Investigator, Grant recipient.